Mushroom body output differentiates memory processes and distinct memory-guided behaviors. - Ichinose, T.; Kanno, M.; Wu, H.; Yamagata, N.; Sun, H.; Abe, A.; Tanimoto, H. (Current Biology, 2021)
The mushroom body (MB) of Drosophila melanogaster has multiple functions in controlling memory and behavior.1-9 However, circuit mechanisms that generate this functional diversity are largely unclear. Here, we systematically probed the behavioral contribution of each type of MB output neuron (MBON) by blocking during acquisition, retention, or retrieval of reward or punishment memories. We evaluated the contribution using two conditioned responses: memory-guided odor choice and odor source attraction. Quantitative analysis revealed that these conditioned odor responses are controlled by different sets of MBONs. We found that the valence of memory, rather than the transition of memory steps, has a larger impact on the patterns of required MBONs. Moreover, we found that the glutamatergic MBONs forming recurrent circuits commonly contribute to appetitive memory acquisition, suggesting a pivotal role of this circuit motif for reward processing. Our results provide principles how the MB output circuit processes associative memories of different valence and controls distinct memory-guided behaviors.